Essays on Venture Capital Investment - WU, Changjian (2023)
The thesis focuses on Venture Capital (VC) investments. This thesis contributes to the VC literature and advances the understanding of venture capital by shedding light on the interplay between VC local experience and geographic distance on investment decisions and partnership performance, impact of VC diversification strategies, and the role of VC monitoring in enhancing director accountability.